The risk of urinary tract infection in children with nephrotic syndrome - Patricia Y. Gunawan; Adrian Umboh (Indonesian Pediatric Society, 2016)
Background Urinary tract infections (UTI) may affect any part of the urinary system: the kidneys, ureters, bladder, or urethra. Nephrotic syndrome (NS) is the most common glomerular disorder in childhood, comprising a group of symptoms that include proteinuria, hypoalbuminemia, hypercholesterolemia, and edema. The prevalence of UTI in NS patients is high, around 25-66.7%. The increased prevalence of UTI in NS is due to immunoglobulin loss, defective T cell function, the presence of ascites, and relative malnutrition.Objective To study the risk of UTI in children with NS.Methods We performed a retrospective study of NS and UTI patients from January 2004 to December 2013 in the Division of Nephrology at Prof. Dr. R.D. Kandou Hospital, Manado. Data was collected from medical records. Diagnosis of UTI was made based on urine culture results. Diagnosis of NS was made based on the group of symptoms mentioned above. Analysis was done using Chi-square test with SPSS version 22 software.Results Of 74 NS patients, 34 (46%) had UTIs. During the same study period, 117 patients had UTIs. NS was more common in boys (64.9%), while NS with UTI was more common in girls (67.6%). The most common organisms causing UTI in NS patients were Eschericia coli and Citrobacter diversus (23% each). Imipenem and amikacin were most commonly used antibiotics to which the bacteria were sensitive. Increased risk of UTI was significant in children with NS (OR 1.8; P=0.03).Conclusion Children with NS are at significantly increased risk of UTIs.